Descriptive Analysis of Oral Cancer Cases in a Tertiary Hospital in Bangladesh - Parvin, Sadia; Lucky, Jesmin Sultana; Shampa, Shaila Afrin; Alim, Samiul; Fatema, Sadia Binte; Hossain, Md Shahadat (Journal of Contemporary Dental Sciences, 2026)
Background: Oral cancer is a significant public health burden in Bangladesh, with limited local evidence on patient profiles, risk factors, and clinical presentation. Methods: A descriptive cross-sectional study was conducted from October 2024 to February 2025 at a Dhaka hospital, including 148 clinically diagnosed oral cancer patients via purposive sampling. Data were collected through structured interviews and standardized oral examinations. Analysis employed descriptive statistics and Chi-square tests in SPSS. Results: The mean age was 58.26 years with male predominance [62%]. High-risk behaviors were prevalent: 84.5% used tobacco/betel quid, 77.7% had low fruit/vegetable intake, and 8.1% consumed alcohol. Advanced clinical features included rapid lesion growth [69.6%], fixation [87.8%], palpable lymph nodes [64.9%], everted edges [56.8%], and whitish mucosa [54.1%]. Age was significantly associated with lesion growth speed [p<0.001], but no significant links were found for tobacco use and lesion edge, gender and lesion edge, or occupation and symptom duration. Conclusion: Findings highlight a high burden of modifiable risk factors and late-stage diagnosis, emphasizing the need for targeted prevention, cessation programs, and opportunistic screening for earlier detection. J. Contemp. Dent. Sci. 2026;14(1): 3-8